Electric field and carrier concentration distributions in the semiconductor under photorefractive Gunn effect - Gorley, P.M.; Horley, P.P.; Chupyra, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
In the framework of the one-dimension field model of semiconductor simultaneosly subjected to the action of carrier-warming electric field and two quasi-monochromatic light waves the authors have numerically calculated the spatial-temporal distributions of inner electric field Е(x,τ) and conductivity band electrons n(x,τ) in dependence on external control parameters (intensity of the incident light waves, their wave vector, external electric field and doping impurity concentration). It was found that the device operating on the base of photorefractive Gunn effect may be controllably switched between three following operation modes: low- and high-light wave intensity as well as a transition mode. The influence of the external control parameters on the Е(x,τ) distribution was determined for each mode in question. It was shown that one could efficiently control the refractive index increment nΔ by means of proper change of the control parameters.